2006
DOI: 10.2337/diabetes.55.02.06.db04-1575
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Gene and Protein Expression of Exocytotic Soluble N-Ethylmaleimide Attachment Protein Receptor Complex Proteins in Pancreatic Islets of Type 2 Diabetic Patients

Abstract: Exocytosis of insulin is dependent on the soluble N-ethylmaleimide attachment protein receptor (SNARE) complex proteins in the B-cells. We assessed insulin release as well as gene and protein expression of SNARE complex protein in isolated pancreatic islets of type 2 diabetic patients (n ‫؍‬ 4) and nondiabetic control subjects (n ‫؍‬ 4). In islets from the diabetic patients, insulin responses to 8.3 and 16.7 mmol/l glucose were markedly reduced compared with control islets (4.7 ؎ 0.3 and 8.4 ؎ 1.8 vs. 17.5 ؎ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
175
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 47 publications
18
175
1
2
Order By: Relevance
“…Since a number of articles have recently reported that ER stress may be implicated in beta cell dysfunction and death in diabetes [10][11][12][13][14][15][16][19][20][21][22][23][24][25][26], in the present study we evaluated features of ER function/dysfunction in human beta cells from type 2 diabetic organ donors. First, we confirmed that diabetic beta cells have functional and survival defects, as previously shown by us and others [27,28,[35][36][37][38]. Specifically, decreased glucosestimulated insulin release and increased apoptosis were observed ( Figs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since a number of articles have recently reported that ER stress may be implicated in beta cell dysfunction and death in diabetes [10][11][12][13][14][15][16][19][20][21][22][23][24][25][26], in the present study we evaluated features of ER function/dysfunction in human beta cells from type 2 diabetic organ donors. First, we confirmed that diabetic beta cells have functional and survival defects, as previously shown by us and others [27,28,[35][36][37][38]. Specifically, decreased glucosestimulated insulin release and increased apoptosis were observed ( Figs.…”
Section: Discussionsupporting
confidence: 89%
“…1c). These findings corroborate previous observations [27,28,[35][36][37][38] and confirm that pancreatic beta cells in human type 2 diabetes have impaired function and increased demise.…”
Section: Islet Insulin Secretion and Apoptosissupporting
confidence: 92%
“…The integrity of the exocytotic machinery is critical for glucose homeostasis, as observed in the Goto-Kakisaki rat model of type 2 diabetes and in type 2 diabetic patients, in both of which the expression of SNARE proteins is decreased [38,39]. In view of the present knowledge on granule dynamics and distinct pools, it has been speculated that the proteins of the exocytotic machinery that are implicated in the rate-limiting priming of secretory granules are strong candidates for the triggering of beta cell dysfunctions associated with type 2 diabetes [40].…”
Section: Discussionmentioning
confidence: 99%
“…At resting or basal conditions, there were no differences between control and SYN-3 knockdown cells in total number of SGs, the number of SGs that were morphologically docked (<50 nm from PM [23]), or number of SGs close to the PM (within 120 nm). However, after stimulation with 11.1 mmol/l glucose plus 10 nmol/l GLP-1 to greatly potentiate the recruitment of SGs to the PM [8], the number of docked SGs (Fig.…”
Section: Syn-3 Is a T-snare On Sgsmentioning
confidence: 93%